Repeated Administration Effects on Psychomotor Vigilance Test Performance. Issue 1 (8th November 2017) - Basner, Mathias; Hermosillo, Emanuel; Nasrini, Jad; McGuire, Sarah; Saxena, Salil; Moore, Tyler M; Gur, Ruben C; Dinges, David F
Abstract: Study Objectives: The Psychomotor Vigilance Test (PVT) is reported to be free of practice effects that can otherwise confound the effects of sleep loss and circadian misalignment on performance. This differentiates the PVT from more complex cognitive tests. To the best of our knowledge, no study has systematically investigated practice effects on the PVT across multiple outcome domains, depending on administration interval, and in ecologically more valid settings. Methods: We administered a validated 3-minute PVT (PVT-B) 16 times in 45 participants (23 male, mean ± SD age 32.6 ± 7.3 years, range 25–54 years) with administration intervals of ≥10 days, ≤5 days, or 4 times per day. We investigated linear and logarithmic trends across repeated administrations in 10 PVT-B outcome variables. Results: The fastest 10% of response times (RT; p lin = .0002), minimum RT ( p log = .0010), and the slowest 10% of reciprocal RT ( p log = .0124) increased while false starts ( p log = 0.0050) decreased with repeated administration, collectively decreasing RT variability ( p log = .0010) across administrations. However, the observed absolute changes were small (e.g., −0.03 false starts per administration, linear fit) and are probably irrelevant in practice. Test administration interval did not modify the effects of repeated administration on PVT-B performance (all p > .13 for interaction). Importantly, mean and median RT, response speed, and lapses, which are among the most frequently used PVT outcomes, did not change systematically with repeated administration. Conclusions: PVT-B showed stable performance across repeated administrations. Combined with its high sensitivity, this corroborates the status of the PVT as the de facto gold standard measure of the neurobehavioral effects of sleep loss and circadian misalignment.